Pengaruh Perkawinan Usia Muda Terhadap Tingkat Perceraian Dini (Studi Kasus Pengadilan Agama Kisaran) - Uswatun Hasanah (Smart Education, 2018)
This study wants to explore and discover directly why the divorce case due to early marriage is increasing in the city range, and the factors that led to the rise of divorce cases in the City range.This study included field research (field research) with qualitative types, which is a primary research where data is collected by direct observation and interviews with competent parties as well as through the documentation of the data contained in the Office of Religious Court of range. While the approach used in this study is a normative approach, which is based on the texts of the Qur'an, Al-Hadith and Qawa'idulUsuliyah and juridical approach, which is based on Islamic law and the Marriage Act of 1974.This research data analysis method using an inductive pattern, the analysis departing from concrete facts or events in the field and then drawn the conclusion of a general nature. And, this research is descriptive-analytical, the research attempted to describe divorce as a result of early marriage Kota range, then analyzed to find the essence of the problem of research. Keywords: marriage at a young age, divorce, religious courts